Mechanistic study of homoleptic trisamidolanthanide-catalyzed aldehyde and ketone hydroboration. Chemically non-innocent ligand participation. Issue 12 (1st March 2023) - Rothbaum, Jacob O.; Motta, Alessandro; Kratish, Yosi; Marks, Tobin J.
Abstract : Experimental and theoretical studies of rapid aldehyde and ketone hydroboration catalyzed by a commercially available homoleptic lanthanide-organic catalyst reveals chemically non-innocent ligand participation. Abstract : Carbonyl bond hydroboration is a valuable synthetic route to functionalized alcohols but relies on sometimes unselective and sluggish reagents. While rapid and selective aldehyde and ketone hydroboration mediated by trisamidolanthanide catalysts is known, the origin of the selectivity is not well-understood and is the subject of this contribution. Here the aldehyde and ketone HBpin hydroboration reaction mechanisms catalyzed by La[N(SiMe3 )2 ]3 are investigated both experimentally and theoretically. The results support initial carbonyl oxygen coordination to the acidic La center, followed by intramolecular ligand-assisted hydroboration of the carbonyl moiety by bound HBpin. Interestingly, ketone hydroboration has a higher energetic barrier than that of aldehydes due to the increased steric encumbrance and decreased electrophilicity. Utilizing NMR spectroscopy and X-ray diffraction, a bidentate acylamino lanthanide complex associated with the aldehyde hydroboration is isolated and characterized, consistent with the relative reaction rates. Furthermore, an aminomonoboronate–lanthanide complex produced when the La catalyst is exposed to excess HBpin is isolated and characterized by X-ray diffraction, illuminating unusual aminomonoboronate coordination. These results shed new light on the origin of the catalytic activity patterns, reveal a unique ligand-assisted hydroboration pathway, and uncover previously unknown catalyst deactivation pathways.